Genomic Regions Responsible for Grain Zinc and Iron Concentration, Yield and Related Traits in Two RILs Population of Rice (Oryza sativa L.) (2018)
Biofortification of rice with micronutrients is widely recognized as a sustainable strategy to alleviate human zinc (Zn) and iron (Fe) deficiencies in developing countries where rice is the staple food such as the Philippines. Major challenges for biofortification in rice are low Zn and Fe uptake, transport and loading into the grain. To date, the genetic mechanisms underlying grain Zn and Fe accumulation in rice have not been fully explored. In this study, genomic regions responsible for grain Zn and Fe concentration, yield and related traits were investigated in 197 and 348 recombinant inbred lines (RILs) of population 1 (IR14M141/Jamir) and population 2 (IR14M141/Kaliboro), respectively. The high Zn donor lines Jamir and Kaliboro were crossed with irrigated breeding line IR14M141. RILs were phenotype for days to 50% flowering, plant height, panicle length, thousand grain weight, grain length, grain width, yield, Zn, and Fe in 2017 Dry Season and Wet Season. The population showed a normal distribution for all traits. Using SNP markers covering the 12 chromosomes, genetic maps were constructed by ICIM software version 4.1 for QTL analysis spanning 1718.65 cM (P1) and 1347.89cM (P2) with an average interval size of 3.75 cM(P1) and 3.33 (P2), respectively. A total of 44 loci responsible for yield and related traits and 11 for grain Zn and Fe concentrations were identified explaining 3.96% to 40.07% of the phenotypic variance. QTLs qPH1.1,qPH2.1 , qPH7.1 ,qTGW5.1 , qGL6.2, qGW3.2, qZn5.1, qZn5.2, qZn6.1, qZn12.1, and qFE7.2 were consistently expressed in two seasons. Across population, QTLS for Zn in Chr 5 at 21.51-26.16 Mb were consistently detected. Among the 11 identified consistent QTLs, qPH1.1, qZn5.1 and qZn5.2 recorded PVE>15%. Thus, fine mapping of consistent QTLs associated with Zn in these populations might be useful for marker development and biofortification breeding in rice.